2020
DOI: 10.3389/fpsyg.2020.519330
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Vulnerable/Grandiose Narcissism and Emotion Regulation

Abstract: Loeffler et al. Emotion Regulation in Narcissism vulnerable narcissism is associated with psychological problems and the use of rather maladaptive emotion regulation strategies, i.e., suppression. Future research should investigate the relationship between pathological narcissism and emotion regulation also by extending the scope to other relevant regulation strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 53 publications
(90 reference statements)
1
14
1
1
Order By: Relevance
“…This could lead to the conclusion that higher levels of identity integration and self-control partially explained a negative association between grandiose narcissism and criminal behavior, and lower levels of identity integration and self-control fully explained the positive association between vulnerable narcissism and criminal behavior. Our result is in line with previous finding showing that grandiose narcissism is not necessarily associated with criminal behavior [ 13 ] and that narcissistic vulnerability, but not grandiosity, is a stronger indicator of aggressive behavior and hostility ([ 31 , 32 , 73 ]; but see [ 20 , 22 ]). People high on narcissistic vulnerability often use inappropriate emotion-regulating strategies, which might lead to more anger and aggression (e.g., 13, [ 31 , 32 ]).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This could lead to the conclusion that higher levels of identity integration and self-control partially explained a negative association between grandiose narcissism and criminal behavior, and lower levels of identity integration and self-control fully explained the positive association between vulnerable narcissism and criminal behavior. Our result is in line with previous finding showing that grandiose narcissism is not necessarily associated with criminal behavior [ 13 ] and that narcissistic vulnerability, but not grandiosity, is a stronger indicator of aggressive behavior and hostility ([ 31 , 32 , 73 ]; but see [ 20 , 22 ]). People high on narcissistic vulnerability often use inappropriate emotion-regulating strategies, which might lead to more anger and aggression (e.g., 13, [ 31 , 32 ]).…”
Section: Discussionsupporting
confidence: 93%
“…In contrast, vulnerable narcissism entails pronounced self-absorbedness, low self‐esteem, hypervigilance, shyness, social withdrawal and emotional hypersensitivity [ 11 , 12 ]. Recent studies have shown that grandiose narcissism is less harmful to mental health, while vulnerable narcissism is associated with psychological problems and the use of rather inappropriate emotion regulation strategies, such as aggression and repression [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…While GN is generally associated with better psycho-social functioning, life satisfaction, and psychological health (1, 2), VN is related to neuroticism (51), higher psychological distress and depressive symptoms (1,52), and less life satisfaction (2). It is also associated with difficulties in accessing adaptive emotion regulation strategies (53) and overall considered to be more dysfunctional.…”
Section: Grandiose and Vulnerable Narcissismmentioning
confidence: 99%
“…Due to the seemingly contradicting manifestations of narcissism, understanding the underlying mechanisms is of both theoretical and practical importance. On the one hand, narcissism, as a personality trait, is related to numerous positive factors such as socio-economic success, overall life satisfaction, as well as psychological health (1,2). On the other hand, high expressions on the continuum of narcissism are associated with proneness to emotional crisis, attachment anxieties, problematic long-term relationships, and severe problems in psychotherapy such as emotional reticence, unwillingness to change, and a higher dropout rate (3)(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…КЛИНИЧЕСКАЯ ПСИХОЛОГИЯ отражающие уязвимое представление личности о себе (Клепикова и Нестерова, 2011). Это сопровождается переживанием собственной хрупкости и уязвимости перед внешним миром, а также выраженной тревогой и интенсивным ощущением одиночества, что по данным Loeffler, Huebben, Radke, Habel, & Derntl (2020) ассоциируется с депрессивными переживаниями и ангедонией. Аналогичные данные представлены Lysaker et al (2012), где описываются стереотипные тревожные и депрессивные реакции людей, блокирующие возможность снижения интернализованной стигмы.…”
Section: обсуждение результатовunclassified